BOARD STRUCTURE AND ASSET QUALITY OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Abdulazeez, Daniya Adeiza; Lawal, Tajudeen; Ibrahim, Mohammed Yabagi (Jurnal Riset Akuntansi dan Keuangan, 2019)
Board Structure (Board Size and Board Independence) of banks is an essential ingredient for ensuring healthy financial intermediation as well as effective management of banksâ€™ asset quality. However, the asset quality of banks in Nigeria continues to deteriorate even amidst various efforts by regulatory authorities to sanitize the Nigerian banking industry. It is on the strength of this backdrop that this study examined the impact of Board structure (Board size and Independence) on the asset quality NPL and LDR) of listed deposit money banks in Nigeria for a period of 10 years (2008-2017). Data for the study were quantitatively retrieved from the annual reports and accounts of the fifteen (15) studied banks. Various robustness tests were carried out to ascertain; the existence of multi-collinearity or otherwise, fitness of the model and to establish the appropriate regression analysis that befits the study. Descriptive statistics, correlation and OLS Robust regression were used to describe and analyze the data. It was found that board structure proxies showed no significant impact on Asset Quality. The study therefore recommended among others that; board independent directors should be encouraged to take their responsibilities seriously in order to help improve banksâ€™ asset quality.Â